Management cycle in cooperation between higher education institutions and enterprises - Tatyana O. Platonova (Высшее образование в России)
The article is about the necessity of cooperation between higher education institutions and enterprises in strategic and operational planning. The review of interaction forms is presented, and its classification by compliance to a management cycle is offered.